The ethics of the Global Kidney Exchange programme. Issue 10210 (9th November 2019) - Minerva, Francesca; Savulescu, Julian; Singer, Peter
Summary: The Global Kidney Exchange (GKE) programme seeks to facilitate kidney transplants by matching donor–recipient pairs across high-income, medium-income, and low-income countries. The GKE programme pays the medical expenses of people in medium-income and low-income countries, thus enabling them to receive a kidney transplantation they otherwise could not afford. In doing so, the programme increases the global donor pool, and so benefits people in high-income countries by improving their chances of finding a donor match. Nevertheless, the GKE has been accused of being a form of organ trafficking, exploiting the poor, and involving coercion and commodification of donors. We refute these claims, arguing that the GKE promotes global justice and reduces the potential for people in need of kidneys in low-income and medium-income countries to be exploited. Misguided objections should not be allowed to prevent the GKE from realising its potential to reduce suffering and save the lives of rich and poor patients alike.